2023
DOI: 10.3390/foods12061279
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Animal Fat Replacement by Emulsified Melon and Pumpkin Seed Oils in Deer Burgers

Abstract: Meat products such as burgers contain large amounts of saturated fat and are considered unhealthy foods by a society that is increasingly aware of the impact of food on their health, as there is a widespread idea that the consumption of large amounts of saturated fats is related to cardiovascular diseases, some types of cancer and obesity. The main goal of this study was to reformulate deer burgers by replacing the saturated fat from its composition with emulsions of oil extracted from melon and pumpkin seeds.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Studies have indeed explored various strategies to enhance the health profile of meat burgers. For instance, reformulating deer burgers by substituting saturated fat with emulsions of melon and pumpkin seed oils resulted in burgers with reduced fat content and higher levels of unsaturated fatty acids, which were positively received by consumers (Martínez et al , 2023) Similarly, incorporating a fat substitute made from a lyophilized hydrogel emulsion enriched with encapsulated acai oil into beef burgers led to products with increased polyunsaturated fatty acids, decreased SFAs, improved nutritional indices and reduced cooking loss (Akwetey and Ibrahim, 2022). These findings highlight the potential for innovative fat substitution techniques to create healthier and more nutritious burger options.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have indeed explored various strategies to enhance the health profile of meat burgers. For instance, reformulating deer burgers by substituting saturated fat with emulsions of melon and pumpkin seed oils resulted in burgers with reduced fat content and higher levels of unsaturated fatty acids, which were positively received by consumers (Martínez et al , 2023) Similarly, incorporating a fat substitute made from a lyophilized hydrogel emulsion enriched with encapsulated acai oil into beef burgers led to products with increased polyunsaturated fatty acids, decreased SFAs, improved nutritional indices and reduced cooking loss (Akwetey and Ibrahim, 2022). These findings highlight the potential for innovative fat substitution techniques to create healthier and more nutritious burger options.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, distinct variations were observed in the organization of muscle fibers among beef samples subjected to different oil frying treatments. Muscle fibers in RBW and CW displayed swelling effects along with weakened connective tissue and water loss, resulting in increased inter-fiber spacing [3]. Consequently, it can be inferred that steaks cooked using an oil gel method exhibit enhanced tenderness.…”
Section: Changes In Cooking Lossesmentioning
confidence: 99%
“…With a smoke point typically exceeding 180 • C (356 • F), KPSO exhibits remarkable stability during high temperature cooking methods such as stir-frying and deep-frying, minimizing the risk of smoke generation and scorching [2]. By incorporating natural wax into KPSO to form an oil gel, not only can the thermal stability of KPSO be further enhanced but also additional nutritional benefits can be provided [3]. Previous studies have demonstrated that oil gels prepared by blending waxes with vegetable oils offer a viable alternative to animal fat in meat products, including hamburgers and sausages [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“… Increasing the concentration of beneficial components in foods [ 99 ]. Replacing excessive or unhealthy components (usually macronutrients) with components with positive effects [ 100 , 101 , 102 ]. Improving the bioavailability or stability of recognized functional components or reducing the potential risk of disease [ 102 , 103 , 104 ].…”
Section: Functional Foodmentioning
confidence: 99%
“…Replacing excessive or unhealthy components (usually macronutrients) with components with positive effects [ 100 , 101 , 102 ].…”
Section: Functional Foodmentioning
confidence: 99%